Development Strategy Of Village-Owned Enterprises (Bumdes) As A Social Enterprise In North Bengkulu Regency - Dita Winastia Putri; Suwarni Suwarni; Kresnawati Kresnawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Village-Owned Enterprises (BUMDes) is one of the pillars of community welfare, utilizing local wisdom to turn the potential in each village into a source of income for the village community. The purpose of this study is to analyze the development strategy of Village-Owned Enterprises (BUMDes) that are still categorized as Pioneer level (A). This research uses qualitative descriptive methods and Focus Group Discussions (FGD) to identify issues in the village. The data analysis method employs SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The results of this study indicate that the main internal strength factor in the development strategy of BUMDes in North Bengkulu is clear regulations that support the implementation system of BUMDes. The main weakness is that it has not contributed to the village's original income (PAD). From the external factors, the main opportunity is the potential for local village development and market potential/opportunity. The main threat factor is competition with private entities with similar business units. The priority strategy with the highest TAS score is the development of local wisdom-based business units with support from the government and private sector.